2019
DOI: 10.18699/vj19.494
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of the stem rust resistance genes in the introgression lines of spring bread wheat

Abstract: A total of 57 introgression lines and 11 cultivars of spring bread wheat developed by All-Russian Institute of Plant Protection and cultivated in the Volga Region were analyzed. The lines were obtained with the participation of CIMMYT synthetics, durum wheat cultivars, direct crossing with Agropyron elongatum (CI-7-57) and have introgressions from related species of bread wheat, namely translocations from Ag. elongatum (7DS-7DL-7Ae#1L), Aegilops speltoides (2D-2S), Ae. ventricosum (2AL-2AS-2MV#1), Secale cerea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
6
0
4
Order By: Relevance
“…Появление вирулентных к Sr25 изолятов гриба мы наблюдали при фитопатологическом анализе саратовских популяций возбудителя стеблевой ржавчины с 2016 по 2020 гг. Также была отмечена потеря устойчивости линий с этим геном в лабораторных условиях (Baranova et al, 2019). Анализ полевой устойчивости сортов особенно в вегетационный сезон 2020 г окончательно показал потерю эффективности на территории Поволжья генов устойчивости к стеблевой ржавчине Sr6Agi и Sr25, что также подтверждается данными по потере устойчивости сортов пшеницы с этими генами при эпифитотии стеблевой ржавчины в Татарстане в 2016 году (Василова, 2017).…”
Section: Discussionunclassified
“…Появление вирулентных к Sr25 изолятов гриба мы наблюдали при фитопатологическом анализе саратовских популяций возбудителя стеблевой ржавчины с 2016 по 2020 гг. Также была отмечена потеря устойчивости линий с этим геном в лабораторных условиях (Baranova et al, 2019). Анализ полевой устойчивости сортов особенно в вегетационный сезон 2020 г окончательно показал потерю эффективности на территории Поволжья генов устойчивости к стеблевой ржавчине Sr6Agi и Sr25, что также подтверждается данными по потере устойчивости сортов пшеницы с этими генами при эпифитотии стеблевой ржавчины в Татарстане в 2016 году (Василова, 2017).…”
Section: Discussionunclassified
“…tauschii genome and common wheat lines with introgressions from Aegilops ssp. [ 12 , 15 , 22 ]. The screening carried out in these studies using molecular markers designed for known Sr genes showed that the genotypes contain mainly the Sr25 , Sr31 , Sr24 and Sr17 genes and their combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more than 80 stem rust ( Sr ) resistance genes have been identified in the genome of common wheat and wheat relatives [ 19 ]. The effectiveness of these genes in relation to local Pgt populations and Ug99 biotypes was evaluated [ 20 , 21 , 22 ]. Molecular markers for the identification of Sr genes and for marker-assisted selection (MAS) were developed ( ).…”
Section: Introductionmentioning
confidence: 99%
“…У новых российских сортов пшеницы в основном были идентифицированы гены Sr31 и Sr57. Ген Sr31 на настоящий момент -единственный эффективный ген против всех российских популяций возбудителя стеблевой ржавчины (Baranova et al, 2019). Как упоминалось выше, он интрогрессирован в пшеницу от ржи (Secale cereale L.), локализован в транслокации 1BL.1RS и тесно сцеплен с генами устойчивости к бурой (Lr26) и желтой (Yr9) ржавчинам, а также к мучнистой росе (Pm8).…”
Section: результатыunclassified